2017
DOI: 10.5194/amt-10-3151-2017
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and evaluation of CCD spectroradiometers for ground-based and airborne measurements of spectral actinic flux densities

Abstract: Abstract. The properties and performance of charge-coupled device (CCD) array spectroradiometers for the measurement of atmospheric spectral actinic flux densities (280-650 nm) and photolysis frequencies were investigated. These instruments are widely used in atmospheric research and are suitable for aircraft applications because of high time resolutions and high sensitivities in the UV range. The laboratory characterization included instrument-specific properties like the wavelength accuracy, dark signal, dar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Snow et al (2007) and Barth et al (2016) for example both show that H 2 O 2 is depleted in convective outflow compared to background upper troposphere. In contrast, other studies found that deep convection can be a source of H 2 O 2 in the upper troposphere (e.g., Jaeglé et al, 1997;Prather and Jacob, 1997;Mari et al, 2003;Bozem et al, 2017). Similarly, convection over India during the summer monsoon is a potential source of excess H 2 O 2 in the upper troposphere.…”
Section: Longitudinal Gradientsmentioning
confidence: 86%
“…Snow et al (2007) and Barth et al (2016) for example both show that H 2 O 2 is depleted in convective outflow compared to background upper troposphere. In contrast, other studies found that deep convection can be a source of H 2 O 2 in the upper troposphere (e.g., Jaeglé et al, 1997;Prather and Jacob, 1997;Mari et al, 2003;Bozem et al, 2017). Similarly, convection over India during the summer monsoon is a potential source of excess H 2 O 2 in the upper troposphere.…”
Section: Longitudinal Gradientsmentioning
confidence: 86%
“…Photolysis frequencies were calculated from spectral actinic flux density spectra (280-650 nm) obtained from CCD spectroradiometer measurements on the top and bottom fuselage of the aircraft covering the upper and the lower hemisphere, respectively (Bohn and Lohse, 2017). Recent recommendations of absorption cross sections and quantum yields were used in the calculations, as well as their temperature and pressure dependencies (if available) by taking into account measured static air temperatures and pressures.…”
Section: Other In Situ Measurementsmentioning
confidence: 99%
“…To obtain an approximate dark correction and to widely remove the dark-current-induced spectral structures, the mean dark spectra is subtracted (Bohn and Lohse, 2017). The dark and light signals are discussed separately below.…”
Section: Radiance Calibrationmentioning
confidence: 99%
“…Numerous space-borne spectrometers, such as GOME (Burrows et al, 1999), SCIAMACHY (Bovensmann et al, 1999), GOME-2 (Munro et al, 2016), and OMI (Levelt et al, 2006), have been successfully applied to the global monitoring of atmospheric trace gas distributions. These instruments measure sun radiance backscattered from the Earth's atmosphere in the UV-VIS wavelength range.…”
Section: Introductionmentioning
confidence: 99%